Characteristics and Radiological Risk Assessment of 210Po in Two Organs of Asian Overbite Clam (Potamocorbula laevis), Asian Hard Clam (Meretrix lyrata) and Suminoe Oyster (Crassostrea rivularis) in Coastal Region of Hung Yen Province - Thi Thanh Xuan, Pham; Xuan Quang, Nguyen; Manh Khai, Nguyen; Van Hao, Duong (VNU Journal of Science: Earth and Environmental Sciences, 2025)
This study evaluated the distribution, accumulation potential, and radiological risk of polonium-210 ( 210 Po) in edible tissues (muscle and hepatopancreas) of three bivalve collected in the coastal area of ​​Hung Yen, Vietnam (Asian hard clam (Meretrix lyrata) , Suminoe oyster (Crassostrea rivularis), and Asian overbite clam (Potamocorbula laevis) ). The results showed that 210 Po activity in hepatopancreas was significantly higher than that in muscle tissue. The highest mean value in hepatopancreas was recorded in Asian overbite clam (295 mBq/g), followed by Oyster (80.0 mBq/g) and Asian hard clam (50.8 mBq/g). In muscle tissue, the mean 210 Po activity was highest in oysters (22.8 mBq/g), followed by Asian overbite clam (22.5 mBq/g) and lowest in Asian hard clam (17.3 mBq/g). The bioaccumulation factor (CF) calculated from water samples showed that the hepatopancreas was the organ of high accumulation, with the highest mean value in Asian overbite clams (220), followed by oysters (59.7) and Asian hard clam (37.9). The annual effective dose (AED) from muscle tissue consumption ranged from 0.01 to 0.6 mSv/year, which in some cases may exceed the recommended level of 1 mSv/year for the public. For radiation ecology, the average total dose of 210 Po in the three species (1.57-2.07 µGy/h) was lower than the ERICA reference threshold of 10 µGy/h, except for some samples of Asian overbite clams with peak values ​​exceeding the threshold. Based on the biological characteristics and accumulation ability, the study suggests that Oysters are suitable indicator species for long-term 210 Po radiation monitoring, while Mussels can be used to detect local pollution hotspots. This result provides important data for monitoring marine environmental radiation and orienting safe seafood consumption in Vietnam.